Prophetic Methods of Calling to Allah and Correcting Errors - Saber , Thamer (Islamic Sciences Journal, 2023)
The call to Allah is the best thing words can do, and it is the reason for the survival of charity in this nation, and the call to Almighty God is a reason to enter into God’s vast mercy, and one of the reasons for victory over enemies, empowerment on earth, and repelling punishment from the servants. It is considered as an important requirement for those who wanted to save themselves, and get the greatest rewards, and many good deeds, and among the reasons for the righteousness of people's lives, and the payment of punishment for them, and the prevention of corruption of the ignorant. And that the methods of the prophetic call and the treatment of errors are many, including: the method of teaching and enlightening the ignorant, the method of strengthening faith and strengthening religious scruples, the method of preaching and reminding and motivating the religious scruples that prevent sins, authorship to give the offender an opportunity to start over, and the method of stimulating passion and arousing feelings and jealousy which may weaken the human beings. The method of reprimanding by harsh words and unrelenting beatings, deterrence by establishing legal punishments and expiations, and the method of changing the environment and giving the offender the opportunity to practice his normal life in another environment that does not look at him with the same offensive look at his original place, and the method of abandonment, which is a punishment that makes the offender review himself and help him to return To his surroundings, the method of unrelenting beating, which is the last choice in making a remedy , and looking for other alternatives to relieve the offender to correct his errors.